MARKETING MANAGEMENT STRATEGY; CHALLENGES AND SOLUTIONS IN THE DIGITAL ERA - Zet Ena; Fitria Sari; Darmawanto Darmawanto; Irsyad Kamal; Ariyanto Masnun (Jurnal Ekonomi, 2023)
This research examines the analysis of good marketing management strategies, challenges, and solutions in the digital era. The research used in this research is a qualitative research which is described descriptively. Various sources were processed in this study such as books, research results, journals, and research articles. In this study, it was explained that the challenges and opportunities for marketing businesses that rely on digital applications are currently felt to be very diverse and complex. The pattern of spending on basic needs and shopping has changed due to the ease of using the internet for shopping and the existence of online services. Digital-based marketing for a profitable and sustainable business is proven to face many challenges and opportunities. The problem is that not all business people and customers understand and can apply technology, while the opportunity is that digital technology applications can innovate business marketing efforts efficiently, effectively, and productively. In addition, the role of digital marketing on the financial performance of several organizations and the implications of digital transformation models have been identified as the most important aspects.